2022
DOI: 10.1021/acs.inorgchem.1c03345
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Tuning the Jahn–Teller Transition Temperature in NaNiO2

Abstract: NaNiO 2 is a layered material consisting of alternating layers of NaO 6 and Jahn–Teller-active NiO 6 edge-sharing octahedra. At ambient pressure, it undergoes a broad phase transition from a monoclinic to rhombohedral structure between 465 and 495 K, associated with the loss of long-range orbital ordering. In this work, we present the results of a neutron powder diffraction study on powdered NaNiO 2 as a function of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…In the main text, we showed that the van Vleck parameter Figure S4: The pressure dependence of bond length distortion index, effective coordination, quadratic elongation, and the van Vleck ρ 0 parameter, for NaO 6 octahedra in NaNiO 2 as a function of pressure, using crystal structures previously reported in Ref. 13 However, we caution that ρ 0 may give a large result for coordination octahedra around Jahn-Teller-inactive cations when the symmetry of the distortion matches the…”
Section: Along Different Axesmentioning
confidence: 67%
See 4 more Smart Citations
“…In the main text, we showed that the van Vleck parameter Figure S4: The pressure dependence of bond length distortion index, effective coordination, quadratic elongation, and the van Vleck ρ 0 parameter, for NaO 6 octahedra in NaNiO 2 as a function of pressure, using crystal structures previously reported in Ref. 13 However, we caution that ρ 0 may give a large result for coordination octahedra around Jahn-Teller-inactive cations when the symmetry of the distortion matches the…”
Section: Along Different Axesmentioning
confidence: 67%
“…The structural effect of a rotation of within a range of 120 can be quite significant, as shown in Fig. 3; such changes can manifest as a JT-elongated (compressed) octahedron with four short (long) and two long (short) bonds [such as NiO 6 in NaNiO 2 (Nagle-Cocco et al, 2022)] or two short, two medium and two long bonds [such as LaMnO 3 (Rodriguez-Carvajal et al, 1998)].…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations